Field study 1 : a guide for 21st century student teachers - Pawileen, Greg Tabios; Reyes, Ericson M.; Rivera, John Amiel; Sison, Trixie Marie J. (Manila : Rex Book Store, 2019)
This textbook on Field Study I was conceptualized to immerse student teachers to actual classroom situation and learning environment where direct observation of teaching and learning focuses on the application of educational theories. It will guide student teachers in developing their level of pedagogical content knowledge, classroom management, and skills in assessment to effectively implement the K-12 Basic Education Curriculum.
Chapter I: Content knowledge and pedagogy 1 -- Chapter II: The Learning environment 41 -- Chapter III: Diversity of learnings 63 -- Chapter IV: Curriculum and Planning 89 -- Chapter V: Assessment and reporting 119 -- Chapter VI: Community linkages and professional engagement 145 -- Chapter VII: Professional growth abd professional development 169
Includes bibliographical references and index.
Keywords: EDUCATIONAL EVALUATION -- PHILIPPINES